AI-Powered Automated Assessment: Aiken Index Analysis of Content Validity Scientific Literacy Asesment - Yamtinah, Sri; Putri, Bela Anisa; Shidiq, Ari Syahidul; Widarti, Hayuni Retno; Wiyarsi, Antuni (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
This study aims to analyze the content validity of the Scientific Literacy Asesment (SLA) instrument, which integrates ethnochemistry based on artificial intelligence through expert agreement based on the Aiken index so that the instrument can measure what should be measured. The research method used is a qualitative descriptive method based on the results of content validity calculated through the Aiken formula. Content validity data were obtained from 10 experts, namely, chemistry education lecturers from UNS, UNY, and UM and high school chemistry teachers in Surakarta, through focus group discussions (FGDs). Content validity is assessed by a score of 1 – 4, namely, irrelevant (TR) with a score of 1; less relevant (KR) with a score of 2; quite relevant (CR) with a score of 3; and relevant (R) with a score of 4 for each question item with aspects measured, namely, aspects of content, language, and construct. Based on the calculation, 15 questions were declared valid with an Aiken index value ≥ 0.73.